Prototype Modelling in Social-Emotional Education At the Example of a COVID-19 Online Learning Environment - Kvieskiene, Giedre; Kvieskiene, Giedre; von Carlsburg, Gerd-Bodo (Peter Lang, 2022)
The authors$1 (Banalyses of innovations in social and socio-emotional education contribute to systematizing distance learning to represent children$1 (Bs and young people$1 (Bs socio-emotional competences and to model how they can be developed. Low social capital and poor mental health, a key feature of the COVID-19 pandemic, are leading to an increasing number of suicides among youth and adolescents. These factors, reflecting the changing social-emotional feelings of children, adolescents and teachers in schools during COVID-19, require a new vision and support for learning practices. Modelling a SEEP in the authors$1 (Bvision would integrate family support, support for every teacher and child, success stories in the development of emotion therapy, and integrated practice in social pedagogical institutions, private initiatives and non-governmental organizations (NGOs).s